SCARECROW‐LIKE23 and SCARECROW jointly specify endodermal cell fate but distinctly control SHORT‐ROOT movement. (November 2015) - Long, Yuchen; Goedhart, Joachim; Schneijderberg, Martinus; Terpstra, Inez; Shimotohno, Akie; Bouchet, Benjamin P.; Akhmanova, Anna; Gadella, Theodorus W. J.; Heidstra, Renze; Scheres, Ben; Blilou, Ikram
Summary: Intercellular signaling through trafficking of regulatory proteins is a widespread phenomenon in plants and can deliver positional information for the determination of cell fate. In the Arabidopsis root meristem, the cell fate determinant SHORT‐ROOT (SHR), a GRAS domain transcription factor, acts as a signaling molecule from the stele to the adjacent layer to specify endodermal cell fate. Upon exiting the stele, SHR activates another GRAS domain transcription factor, SCARCROW (SCR), which, together with several BIRD/INDETERMINATE DOMAIN proteins, restricts movement of SHR to define a single cell layer of endodermis. Here we report that endodermal cell fate also requires the joint activity of both SCR and its closest homologue SCARECROW‐LIKE23 (SCL23). We show that SCL23 protein moves with zonation‐dependent directionality. Within the meristem, SCL23 exhibits short‐ranged movement from ground tissue to vasculature. Away from the meristem, SCL23 displays long‐range rootward movement into meristematic vasculature and a bidirectional radial spread, respectively. As a known target of SHR and SCR, SCL23 also interacts with SCR and SHR and can restrict intercellular outspread of SHR without relying on nuclear retention as SCR does. Collectively, our data show that SCL23 is a mobile protein that controls movement of SHR and acts redundantly with SCR to specify endodermal fate in the root meristem. Significance Statement: In plants, cell‐cell trafficking of transcription factors is widely used for intercellular communication during cell fate specification. Here we show that SCARECROW‐LIKE 23 (SCL23) is an additional component of the SCARECROW‐SHORT‐ROOT(SCR‐SHR) complex that can traffic between cell layers, restricting SHR spread and redundantly specifying endodermal fate with its closest homologue SCR.